Structure and formation of ice-ground veins of the second lake-alluvial terrace in the North of Gydan in the late Neopleistocene–Holocene - Ya. V. Tikhonravova; A. V. Lupachev; E. A. Slagoda; V. V. Rogov; A. O. Kuznetsova; V. I. Butakov; G. V. Simonova; N. A. Taratunina; D. R. Mullanurov (Лëд и снег)
The syngenetic ice and ice-ground composite veins in khasyrey (alas) and interalas plateaus were studied on the second lake-alluvial terrace located in the North of the Gydan Peninsula near the village of Gyda. On the basis of the radiocarbon dating, the time of formation of deposits containing veins from was established – from 16 640 to 854 BP. The peat deposits are mainly represented by the following species: Carex sp., Eriophorum  sp., Betula nana, Equisetum  sp., Calamagrostis  sp., Vaccinium vitis-idaea, Drepanocladus  sp., Empetrum sp., Vaccinium uliginosum, Rubus arcticus, Petasites sp. It is established that the polygonal-veined ice of khasyrey and interalas plateaus, except for vertical-striped «clean» ice, contain areas with vertical wavy streaks of ice-ground. Ice of elementary veins and segregation ice were revealed in the composition of veins according to structural and textural features in polarized light. Elementary ice veins compose «clean» ice sections of veins and segregation ice which are their ice-ground sections. Elementary veins are indicative of the predominance of the process of frost cracking during the formation of polygonal-vein ices. The presence of inclusions of ice-ground in the structure of veins points is evidence of a manifestation of local thermokarst processes under the growth of polygonal-vein ice. Ice-ground veins were formed by repeated thawing of the initial ice veins. The formation of ice-ground veins during syngenetic freezing of sediments of the second lake-alluvial terrace is related to uneven manifestation of thermokarst in different facies situations and and climate changes at the Early Pleistocene and Holocene.